The Oosterschelde Estuary (The Netherlands): A Case-Study of a Changing Ecosystem 1994
DOI: 10.1007/978-94-011-1174-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Composition, distribution and biomass of meiobenthos in the Oosterschelde estuary (SW Netherlands)

Abstract: Meiofauna composition, abundance, biomass, distribution and diversity were investigated for 31 stations in summer. The sampling covered the whole Oosterschelde and comparisons between the subtidalintertidal and between the western-central -eastern compartment were made .Meiofauna had a community density ranging between 200 and 17500 ind 10 cm -2, corresponding to a dry weight of 0 .2 and 8 .4 gm-2 . Abundance ranged between 130 and 17 200 ind 10 CM-2 for nematodes and between 10 and 1600 ind 10 cm -2 for copep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
(20 reference statements)
5
16
0
1
Order By: Relevance
“…Nematode density values were similar to those found in communities living in subtidal sediments of northern European estuaries, but the number of genera was relatively lower (Smol et al, 1994;Soetaert et al, 1994). On the other hand, nematode density was lower than in intertidal sediments which are often more diverse (Soetaert et al, 1994(Soetaert et al, , 1995Steyaert et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Nematode density values were similar to those found in communities living in subtidal sediments of northern European estuaries, but the number of genera was relatively lower (Smol et al, 1994;Soetaert et al, 1994). On the other hand, nematode density was lower than in intertidal sediments which are often more diverse (Soetaert et al, 1994(Soetaert et al, , 1995Steyaert et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…Warwick and Gee, 1984;Heip et al, 1985;Li and Vincx, 1993;Smol et al, 1994;Steyaert et al, 2003;RzeznikOrignac et al, 2003). There is a notorious imbalance between the northern European systems, relatively well studied, and the southern ones, which are insufficiently described (Soetaert et al, 1995;Adã o, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For some Sabatieria species such as S. punctata and S. celtica, the contribution of fine sediments seems to be much more important (Vanreusel 1991), but surprisingly this genus was not found in the LTL of Bananal Beach where a high percentage of fine sediments was found. Smol et al (1994) also reported this genus from sites with less than 5% silt. Perhaps its presence is related to the degree of pollution of the bay.…”
Section: Hydrodynamic X Sediment Characteristicsmentioning
confidence: 89%
“…Most specifically, from 168.7 to 1602.6 inds/10 cm² in harbor stations in Italy [18]; 454.0±289.9 -3137.7±337.1 inds/10 cm² in the Mekong estuaries [5]; and 67-1666 inds/10 cm 2 in the Westerschelde [19]; 317-1002 inds/10 cm² in Shin River, Kasuga River, and Tsumeta River in Takamatsu, Japan [20]. However, nematode densities in the Saigon River were lower than that in the Oosterschelde [21] with values of 100-7100 inds/10 cm² or five European estuaries [22] with values from 130-14500 inds/10 cm².…”
Section: Discussionmentioning
confidence: 99%